Optimal compressed representation of high throughput sequence data via light assembly - Antonio A. Ginart (Nature Portfolio, 2018)
Increase in high throughput sequencing (HTS) data warrants compression methods to facilitate better storage and communication. Here, Ginart et al. introduce Assembltrie, a reference-free compression tool which is guaranteed to achieve optimality for error-free reads.